Biodegradable polymer films from seaweed polysaccharides: A review on cellulose as a reinforcement material - H. P. S. Abdul Khalil; Y. Y. Tye; C. K. Saurabh; C. P. Leh; T. K. Lai; E. W. N. Chong; M. R. Nurul Fazita; J. Mohd Hafiidz; A. Banerjee; M. I. Syakir (eXPRESS Polymer Letters)
Seaweed and cellulose are promising natural polymers. This article reviews the basic information and recent developments of both seaweed and cellulose biopolymer materials as well as analyses the feasible formation of seaweed/cellulose composite films. Seaweed and cellulose both exhibit interesting film-forming properties. Nevertheless, seaweed has poor water vapour barrier and mechanical properties, whereas cellulose is neither meltable nor soluble in water or common organic solvents due to its highly crystalline structure. Therefore, modification of these hydrocolloids has been done to exploit their useful properties. Blending of biopolymers is a must recommended approach to improve the desired characteristics. From the review, seaweed is well compatible with cellulose, which possesses excellent mechanical strength and water resistance properties. Moreover, seaweed/cellulose composite films can prolong a product’s shelf life while maintaining its biodegradability. Additionally, the films show potential in contributing to the bioeconomy. In order to widen seaweed and cellulose in biocomposite application across various industries, some of the viewpoints are highlighted to be focused for future developments and applications.